Dynamic of heat production partitioning in rooster by indirect calorimetry - Riveros, Rony Lizana [UNESP]; de Sousa Camargos, Rosiane [UNESP]; Macari, Marcos [UNESP]; de Paula Reis, Matheus [UNESP]; Leme, Bruno Balbino [UNESP]; Sakomura, Nilva Kazue [UNESP] (Asian Australasian Association of Animal Production Societies, 2023)
Objective: The objective of this study was to describe a methodological procedure to quantify the heat production (HP) partitioning in basal metabolism or fasting heat production (FHP), heat production due to physical activity (HPA), and the thermic effect of feeding (TEF) in roosters. Methods: Eighteen 54-wk-old Hy Line Brown roosters (2.916±0.15 kg) were allocated in an open-circuit chamber of respirometry for O2 consumption (VO2), CO2 production (VCO2), and physical activity (PA) measurements, under environmental comfort conditions, following the protocol: adaptation (3 d), ad libitum feeding (1 d), and fasting conditions (1 d). The Brouwer equation was used to calculate the HP from VO2 and VCO2. The plateau-FHP (parameter L) was estimated through the broken line model: HP = U×(R–t)×I+L; I = 1 if t<R or I = 0 if t>R; Where the broken-point (R) was assigned as the time (t) that defined the difference between a short and long fasting period, I is conditional, and U is the decreasing rate after the feed was withdrawn. The HP components description was characterized by three events: ad libitum feeding and short and long fasting periods. Linear regression was adjusted between physical activity (PA) and HP to determine the HPA and to estimate the standardized FHP (st-FHP) as the intercept of PA = 0. Results: The time when plateau-FHP was reached at 11.7 h after withdrawal feed, with a mean value of 386 kJ/kg0.75/d, differing in 32 kJ from st-FHP (354 kJ/kg0.75/d). The slope of HP per unit of PA was 4.52 kJ/mV. The total HP in roosters partitioned into the st-FHP, termal effect of feeding (TEF), and HPA was 56.6%, 25.7%, and 17.7%, respectively. Conclusion: The FHP represents the largest fraction of energy expenditure in roosters, followed by the TEF. Furthermore, the PA increased the variation of HP measurements.
Keywords: Energy Expenditure; Energy Metabolism; Energy Utilization; Metabolic Rate; Rooster